Deranged Function (1997 AIME Problem #12)

Algebra Level 4

The function f f defined by f ( x ) = a x + b c x + d f(x)= \frac{ax+b}{cx+d} , where a a , b b , c c and d d are nonzero real numbers, has the properties f ( 19 ) = 19 f(19)=19 , f ( 97 ) = 97 f(97)=97 and f ( f ( x ) ) = x f(f(x))=x for all values except d c \frac{-d}{c} . Find the unique number that is not in the range of f f .


The answer is 58.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

f ( x ) = a x + b c x + d f(x)=\dfrac {ax+b}{cx+d}

f ( f ( x ) ) = ( a 2 + b c ) x + b ( a + d ) c ( a + d ) x + d 2 + b c \implies f\left (f(x)\right ) =\dfrac {(a^2+bc)x+b(a+d)}{c(a+d)x+d^2+bc}

f ( f ( x ) ) = x f\left (f(x)\right ) =x\implies

c ( a + d ) x 2 + ( d 2 + b c ) x = ( a 2 + b c ) x + b ( a + d ) c(a+d)x^2+(d^2+bc)x=(a^2+bc)x+b(a+d)

Comparing the coefficients of like terms we get a + d = 0 a+d=0

So, f ( x ) = a x + b c x a f(x)=\dfrac {ax+b}{cx-a}

f ( 19 ) = 19 38 a + b = 361 c f(19)=19\implies 38a+b=361c

f ( 97 ) = 97 194 a + b = 9409 c f(97)=97\implies 194a+b=9409c

Solving we get a = 58 c , b = 1843 c a=58c,b=-1843c

So, f ( x ) = 58 x 1843 x 58 f(x)=\dfrac {58x-1843}{x-58}

So, the domain of f ( x ) f(x) is ( , 58 ) ( 58 , ) (-\infty, 58)\cup (58,\infty)

For x 58 , ( x 58 ) f ( x ) = 58 x 1843 x\neq 58,(x-58)f(x)=58x-1843

If the value of f ( x ) f(x) be 58 58 , then the L. H. S. of the equation is

58 ( x 58 ) = 58 x 3364 58(x-58)=58x-3364

Hence the above equation connecting f ( x ) f(x) is not satisfied for any value of x x

So, 58 58 is not in the range of f ( x ) f(x)

So the only number out of the domain as well as the range of f ( x ) f(x) is 58 \boxed {58} .

ChengYiin Ong
Oct 17, 2020

We can also compute the inverse of f ( x ) f(x) since we have its inverse is the same as itself, y = a x + b c x + d f 1 ( x ) = d x b c x + a y=\frac{ax+b}{cx+d}\implies f^{-1}(x)=\frac{dx-b}{-cx+a} which means that a , b , c a, b, c and d d must be proportional to d , b , c d, -b, -c and a a . Thus, a = d a=-d and the rest follows.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...